Work Engagement in the Work Place: The Role of Procedural Justice, Perceived Organizational Support and Organizational Trust - wibowo, praptini yulianti (Advances in Social Sciences Research Journal, 2015)
Employee engagement in the workplace is very important, especially for the organizational competitive advantage. Employee engagement in the workplace can be built through procedural justice, perceived organizational support and organizational trust. This research is an explanatory research that will explain the causal relationship between variables or through hypothesis testing. The sample in this study was collected through 118 respondents. The criteria of the selected respondents were the ones that working in the production division, since production division is the core of industrial companies. The sampling technique in this study used Partial Least Square. The results of this study supports the relationship between procedural justice and perceived organizational support with employee engagement either directly or with the mediation of organizational trust.